TECHNO PEDAGOGICAL AND CONTENT KNOWLEDGE (TPACK): AN EFFECTIVE TOOL FOR CONTENT DELIVERY FOR TEACHERS - Singh, Neetu; Indian, Ajay (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Teaching is the process of imparting knowledge, skills, and interpersonal abilities to a learner or audience in an educational setting. Teaching is a complicated practice that requires an interweaving of many kinds of specialized knowledge. With the passage of time technology has made an entry in the field of teaching. Advent of computer, television, internet, mobile, interactive white board etc. has brought bigger changes in the field of teaching-learning process. The present era is an era of science and technology and now a days it is required that teachers must be well aware of use of technology in teaching-learning process. New inventions in the field of science and technology have been incorporated in teaching-learning process to make it more interesting and comprehensible for the learners. The introduction of technology in Education sector has given rise to new terminology “Techno Pedagogical Content and Knowledge” also known TPACK. Term TPACK contains various terms viz. ‘Content Knowledge(CK)’, Pedagogical Knowledge (PK), Technological Knowledge (TK), Pedagogical Content Knowledge (PCK), Technological Content Knowledge (TCK), Technological Pedagogical Knowledge (TPK). TPACK is the end result of various combinations and interests, drawing from different terms related with it – and from the three larger underlying areas of content, pedagogy, and technology – in order to create an effective basis for teaching using educational technology.